Reproductive activity and condition index of Holacanthus passer (Teleostei: Pomacanthidae) in the Gulf of California, Mexico - Arellano-Martínez, Marcial; Ceballos-Vázquez, Bertha Patricia (Revista de Biología Tropical, 2001)
Annual variation and relationship between the gonadosomatic index (IG) and the condition index (K) of Holacanthus passer were evaluated in 194 specimens from Cueva de León, Gulf of California (24°02’ N, 110°24’ W). There was a significant negative correlation between IG and K in both sexes: indices exhibit an opposite seasonal pattern. The reproductive activity of both sexes is inversely related with nutritional status. There was a significant difference in IG but not in K values between males and females. The condition index may be used to determine reproduction time of the species in other localities without sacrificing the organisms. This could be a valuable tool to develop monitoring programs for fisheries and culture of this species.